Dekada '70 a dramaturgical-based adaptation of Lualhati Baustista's dekada '70 into a new musical - Valera, Patrick James M.; Bonifacio-Ramolete, Amihan (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This study is about the use dramaturgical methods in the process of adapting Filipino novel Dekada '70 of Lualhati Baustista into a stage musical with the following objectives: (1) craft a dramaturgical process for the adaptation of a novel into a musical, (2) provide a strong dramaturgical recommendation to allow the adaptor to focus on the creative writing elements of the play, (3) create a re contextualized stage musical version of Dekada '70 that resonates to the present conditions. By using dramaturgical methods such as Production Dramaturgy, New Play Dramaturgy, the usage of the two as proposed by Barnette's Adaptation Dramaturgy, alongside with methods providing context, relationship, and structure distinct to the novel, a new dramaturgical process was created distinct to the adaptation of the particular novel . The findings show that the process allowed for a strengthened relationship with the source author, a dynamic context for content and intent, and a dramaturgical recommendation that allowed for the adaptor to focus on the text and lyrics of the musical. The study concludes that although this process is distinct to the transformation of Dekada '70 into a stage musical, methods synthesized, discovered, and implemented can serve as guide and inspiration for dramaturgs who want to embark on adaptation.
Thesis (Bachelor of Arts in Theatre Arts)--University of the Philippines Diliman